Illuminating Enterprise and Entrepreneurship Education - Matlay, Harry (Education + training ; volume 55, number 8/9, 2013, 2013)
This eBook aims to critically examine and empirically evaluate a range of important aspects related to the fast growing topic of Enterprise and Entrepreneurship Education. The articles provide a critical perspective on various aspects linked to enterprise and entrepreneurship education. This subject is a rapidly expanding field of research and its range of outputs is not only of interest, but also relevant to a large and varied group of stakeholders. Individually and cumulatively, these papers illuminate both the growth and the variety of concepts, contexts and methodologies covered in this ar.